PERHITUNGAN PAJAK PROGRESIF KENDARAAN BERMOTOR DALAM UPAYA MENINGKATKAN PENDAPATAN ASLI DAERAH - Made Sutrasmini; Anantawikrama Tungga Atmadja (Jurnal Widya Akuntansi dan Keuangan, 2021)
The research aims to find out the progressive tax calculation mechanism for motor vehicles. The subject of this research is the office of UPTD Tax Service and the regional levy of Bali Province in Bueleleng district and the object of progressive tax calculation mechanism of motor vehicles in Uapaya increase regional revenue. Methods of data collection with documentation and observation methods are further analyzed with quantitative descriptive analysis techniques. Results of this study showed that the calculation mechanism of the motor vehicle Progressive tax in the office of UPTD Tax Service and Levy of Bali Province in Bueleleng district, in conducting tax taxpayer payment requires progressive tax calculation mechanism of vehicle Bermootor. Based on research results there are barriers to note that is lack of understanding of the mechanism of progressive tax calculation. The solution given to the constraints is to disseminate to the taxpayer regarding the mechanism of progressive tax calculation in tax payments.